2020
DOI: 10.1186/s12889-020-10007-w
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal patterns of malaria incidence in Uganda using HMIS data from 2015 to 2019

Abstract: Background As global progress to reduce malaria transmission continues, it is increasingly important to track changes in malaria incidence rather than prevalence. Risk estimates for Africa have largely underutilized available health management information systems (HMIS) data to monitor trends. This study uses national HMIS data, together with environmental and geographical data, to assess spatial-temporal patterns of malaria incidence at facility catchment level in Uganda, over a recent 5-year … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Modelled national parasite prevalence predictions have been used to inform sub-national approaches to malaria control in Kenya [ 12 , 13 ], Uganda [ 14 ], Somalia [ 15 , 16 ], Namibia [ 17 ], Senegal [ 18 ], Cote D’Ivoire [ 19 , 20 ], Malawi [ 21 23 ], Angola [ 24 ], Madagascar [ 25 ], Ghana [ 26 ], Rwanda [ 27 , 28 ], Mozambique [ 29 , 30 ], Burkina Faso [ 31 ], Sudan [ 32 ] and Tanzania [ 33 35 ]. The use of routine health facility data sources to define malaria incidence has increased in recent years, in combination with parasite prevalence or independently, in Namibia [ 36 ], Zambia [ 37 ], Malawi [ 38 ], Tanzania [ 34 , 35 , 39 ], Madagascar [ 40 42 ], Zimbabwe [ 43 ], Ghana [ 44 ], Burkina Faso [ 45 ] and Uganda [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modelled national parasite prevalence predictions have been used to inform sub-national approaches to malaria control in Kenya [ 12 , 13 ], Uganda [ 14 ], Somalia [ 15 , 16 ], Namibia [ 17 ], Senegal [ 18 ], Cote D’Ivoire [ 19 , 20 ], Malawi [ 21 23 ], Angola [ 24 ], Madagascar [ 25 ], Ghana [ 26 ], Rwanda [ 27 , 28 ], Mozambique [ 29 , 30 ], Burkina Faso [ 31 ], Sudan [ 32 ] and Tanzania [ 33 35 ]. The use of routine health facility data sources to define malaria incidence has increased in recent years, in combination with parasite prevalence or independently, in Namibia [ 36 ], Zambia [ 37 ], Malawi [ 38 ], Tanzania [ 34 , 35 , 39 ], Madagascar [ 40 42 ], Zimbabwe [ 43 ], Ghana [ 44 ], Burkina Faso [ 45 ] and Uganda [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Country-specific studies in Uganda have shown that the use of ITNs [ 11 ] and IRS [ 12 ] have reduced the occurrence of malaria in areas where they have been used. However, despite all these efforts, the burden of malaria in many parts of the country is still high [ 1 , 5 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data collection occurred over the warm, dry season months that are typically low-incidence for ARI and malaria and may underestimate the case numbers and hypoxaemia prevalence in other seasons. 47 At the time of this study (February to April 2021), Uganda was experiencing the COVID-19 pandemic, with data collection commencing shortly after a second major wave of infections had subsided and restrictions loosened in January 2021. While we observed similar service activity compared to previous years, changes in care-seeking, hygiene and social behaviour may have influenced participant characteristics and reduced the prevalence of ARI.…”
Section: Discussionmentioning
confidence: 99%